On Edge Irregular Total Labeling Algorithm of Cycle Chain Graph - Gradina Nur Fauziah (Syntax Corporation, 2022)
Suppose G=(V,E) is a graph with the vertex set V(G) and edge set E(G) we defined a labeling f:V∪E→1,2,…,k to be an edge irregular total k-labeling of graph G if for every two different edge e and f there is wt(e)≠wt(f). The minimum k for which the graph G has an edge irregular total k-labeling is called the total irregularity streghth of the graph G. On this research we found that labeling algorithm of Cycle Chain Graph with n block cycle graph is an edge irregular total labeling